Performance of Mud Bonded Stone Masonry Houses and Mitigation - Parajuli, Hari Ram (Nepal Journal of Science and Technology, 2016)
Mud mortar bonded stone masonry houses are very common in the Himalayan region. These houses perform well under vertical loads; however, their capacity under lateral loads is questionable. Two representative houses are modeled by finite element method and analyzed under site specific earthquake ground motions simulated for the region. Stone walls were modeled as equivalent linear solid elements and interfaces between stones as joint elements. The joints were allowed to slide, open and close satisfying Mohr-Coulomb criteria. Parameters required for analysis were investigated from shaking Table tests. The model houses performed very poor even in 98 years return period earthquakes. As a mitigation measure, modified model houses by adding wooden bond beams were run under same earthquake ground motion as they were run before. Analyses show locally available wooden bond beams can be a good mitigation measure for strengthening of low strength stone masonry houses.